Knowledge, Attitudes, and Practices Related to Covid-19 in College Students - Nida Faradisa Fauziyah; Miftakhul Ulum Mahfud (Disease Prevention and Public Health Journal, 2023)
Background: The world is currently dealing with a new outbreak which is called Covid-19. As a consequence, understanding how students react to a public health emergency is crucial for a school or university. This study is aimed to learn about students' Covid-19 knowledge, attitudes, and practices. The goal of this study is to discover what students know about Covid-19, as well as their views and practices about it. Methods: This research was conducted at a private institution in Surakarta, Indonesia, using a cross-sectional survey with students as the participants adopting purposive sampling. The survey includes a questionnaire on Covid-19 Knowledge, Attitudes, and Practice (KAP) that students voluntarily complete. Result: A total of 476 people were involved in the study comprising 185 males and 291 females ranging in age from 17 to 26. It is found that medical female students had significantly higher knowledge, with p<0.001 and p = 0.023. Based on the overall KAP score, medical female students had better knowledge and a positive attitude (p 0.004). The total score for Knowledge, Attitude, and Practice was 18.95 ± 2,188 with knowledge scores of 3.80 ± 0.848 (range: 0 ~ 5), attitudes of 6.48 ± 1,425 (range: 0 ~ 10), and practice of 8.67± 1.133 (range: 0 ~ 10) respectively. Conclusion: The majority of students have a good understanding of Covid-19 and practice it regularly. However, the overall value of knowledge, attitudes, and practices varies significantly between gender, department, and level.